(untitled) (American Journal of Management, 2022)
Organ transplantation is often studied in its medical, legal or ethical dimensions. Very few works have considered the supply chain dimension, even though the organisation of organ transportation is critical to the success of transplants given the extremely tight time constraint to guarantee the correct state of the organ. The authors examine the logistical systems associated with organ transplantation, distinguishing between two service processes: the push flow model, implemented in the context of legal transplants‚ and the pull flow model, implemented in the context of coercive transplants. While this dual supply chain perspective has never been analysed until now, the research note highlights a theorical gap which could be answered in future research.